Solutions to Enhance Corporate Sales Performance in Vietnam - Nguyen Van Tien, Nguyen Hoang Tien, Boleslaw Rafal Kuc, Leo Paul Dana, Phuoc Minh Hiep, Vu Xuan Ha (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article presents some solutions to improve sales performance in private enterprises in Ho Chi Minh City (Vietnam) in line with the trend of globalization and international economic integration. The article has thoroughly analyzed the theoretical basis of the sales concepts, the role of the sales in business, the and the sales management process and the related practices of those issues in Vietnam.